2014
DOI: 10.1111/ajfs.12046
|View full text |Cite
|
Sign up to set email alerts
|

Volume Information and the Profitability of Technical Trading

Abstract: Past studies have employed market indices to gauge the usefulness of technical trading, disclosing an enigma concerning the technical trading of individual stocks. We, for the first time, applied technical trading rules to each and every stock listed in an emerging equity market. We controlled the vast data set by share turnover that signifies trading volume information. Blending price and volume information, we observed that variable-length moving averages (VMAs) generally outperform the buy-and-hold strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…More recently, Neely and Weller (2013) argue that trading rule returns in foreign exchange markets remain significant but shifted towards emerging markets. Also Chang et al (2014) find evidence for the profitability of moving average trading rules for emerging stock markets. Another argument highlights that the practice could have had merit in any market but that its profitability decreased over time ( Olson, 2004;Qi and Wu, 20 06;Schulmeister, 20 09 ) driven by a continuous increase in market efficiency or to environmental changes suggested by the adaptive market hypothesis ( Lo, 2004 ).…”
Section: Introductionmentioning
confidence: 91%
“…More recently, Neely and Weller (2013) argue that trading rule returns in foreign exchange markets remain significant but shifted towards emerging markets. Also Chang et al (2014) find evidence for the profitability of moving average trading rules for emerging stock markets. Another argument highlights that the practice could have had merit in any market but that its profitability decreased over time ( Olson, 2004;Qi and Wu, 20 06;Schulmeister, 20 09 ) driven by a continuous increase in market efficiency or to environmental changes suggested by the adaptive market hypothesis ( Lo, 2004 ).…”
Section: Introductionmentioning
confidence: 91%
“…The currency investment in creating economies offer up to 20 percent yearly return inside seeing 5 percent yearly price and exchanging rules are consistent after some time (Chong et al, 2009). Some past researches found the more return for technical exchange rules over purchase and hold method for 25 monetary forms out of 39 inside seeing transaction cost, and they finish up the inefficiency of the market like the reason behind the achievement of technical trading rules in predicting the market (Fernández-Pérez et al, 2012;Chang et al, 2014). Tajaddini and Crack (2012) pointed out that profitability of long and short momentum system to be 1 and 3 percent separately resulting to considering the genuine trading price; they moreover demonstrate the abatement in profit for latest 5 years in the sample time span.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Current paper results are comparative with Chang et al (2014) examination of individual stocks in newly established markets; they found an exchange off amongst liquidity and productivity of variable moving average stock returns. We stated an informative association amongst instability and stock returns.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation